The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/00365599.2010.523013
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation in urological indications: The Finnish experience

Abstract: The difference in gender distribution compared with earlier published series may be explained by a selection bias due to the limited referrals of female patients from gynaecologists. The results favour the use of a tined lead device because of the shorter operating room time. Furthermore, the outcome seems to be more favourable among patients with a staged implant procedure compared with a one-stage operation with a tined lead device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Our series is consistent with most retrospective studies reporting on a global SNM experience, which included a predominant population of refractory OAB patients and fewer patients with urinary retention or BPS/IC ( 9 , 10 ).…”
Section: Discussionsupporting
confidence: 87%
“…Our series is consistent with most retrospective studies reporting on a global SNM experience, which included a predominant population of refractory OAB patients and fewer patients with urinary retention or BPS/IC ( 9 , 10 ).…”
Section: Discussionsupporting
confidence: 87%
“…Several authors have demonstrated that advanced patient age, male gender, increased duration of symptoms and the presence of concomitant medical comorbidities decrease the likelihood of success following SNM. [13][14][15][16] The two cohorts examined in our study were similar in age, gender distribution and overall health. As a result, we do not believe that sampling error contributed to our results.…”
Section: Discussionmentioning
confidence: 64%
“…2,[24][25][26][27] Studies on sacral neuromodulation demonstrated that all improvement of quality of life and subjective symptoms. 2,[28][29][30][31] The FDA has already approved injection of intradetrusor onabotulinumtoxinA (100U) as a third-line treatment in nonneurogenic OAB patients. 2 Indwelling catheters remain the last treatment option and are not recommended for OAB.…”
Section: Discussionmentioning
confidence: 99%